Simulation of metallic or dielectric surface nanostructures - Kwek, Zhan Lun (2019)
Transparent display is a rapidly growing technology that allows the projection of images and information onto a clear screen, allowing us to see the background behind it simultaneously. Applications of this technology may range from the windshields of vehicles, aircraft cockpit windows to even regular glass windows along streets. With potential applications across different industries, solutions are being developed offering promising results tailoring to different needs. First, the Head-up Display (HUD) offers a simple solution that works by projecting the image into the users’ eyes through reflection off a beam splitter [1]. This solution only provides a narrow viewing angle, limiting the position of the user, thus meaning that it is only suitable in scenarios when the users are stationary with respect to the beam splitter. Next, frequency-conversion screens are displays that work on the principle of thin layer screens containing fluorescent materials that emit red, green and blue light upon absorbing their corresponding excitation wavebands from ultra-violet light or infrared light [1]. This concept offers good image production however specifically designed projector that can emit the corresponding excitation wavebands is required for this display to function. Already available in the market is the Organic Light Emitting Diode (OLED). Another solution to transparent displays lies in the usage of transparent electrodes indium tin oxide (ITO) glass alongside OLED [2]. Prototypes have already been developed by Samsung and LG but issues of limited lifetime and high susceptibility to water damage lead to the slow permeability into the markets [3]. Lastly Localized Surface Plasmon Resonance (LSPR) based screens are transparent screens that has three different specially engineered nanoparticles embedded, each scattering a specific wavelength of light [4]. This means that light that does not fall into these wavelengths passes through the screen, making the screen transparent. The scattering concept is based on LSPR of metallic nanoparticles. Not only does this solution provide a wide viewing angle, the image produced also would be of high quality due to the selective wavelength scattering. Finally, due to the potential of having the nanoparticles dispersed in a transparent film that can be applied on any glass surfaces, the solutions offers low production cost and scalability to large sizes [4], thus offering a wide range of attractive applications across the industries.